Characteristics of Soft Tychonoff Spaces with New Soft Separation Axioms - Shuker Mahmood (Journal of College of Education, 2021)
The aim of this work is to investigate and study soft Tychonoff space and some new soft spaces such as soft , soft , soft , soft , soft , soft , soft and soft in this work the relationships between these new soft spaces such as soft public regular, soft public normal, soft strongly completely regular, soft semi completely normal and with well known axioms soft , soft and soft are obtained, Further, the relationships between these new soft spaces with each other are studied. We prove that each soft space is soft Tychonoff space, also in this paper we show that each soft space is soft , each soft space is soft and each soft space is soft . Finally, depending on the above soft spaces and properties of the soft fuzzy spaces, the new types of soft fuzzy spaces can be introduced like Soft fuzzy public regular, Soft fuzzy strongly completely regular, and others.